Assessment of procurement, distribution, availability, and utilization of rabies biologicals for postexposure prophylaxis in seven states of India - Ashwath Narayana D Hanumanthaiah; Ravish Shankaraiah Haradanhalli (Wolters Kluwer Medknow Publications, 2019)
Background: To achieve the elimination of dog-mediated human rabies by 2030, all bite victims shall have access to life-saving rabies biologicals across the country. The information on procurement, distribution, availability, and utilization of rabies biologicals for postexposure prophylaxis is insufficient. Objectives: The objective of the study is to assess the demand, procurement, distribution, availability, storage, and utilization of rabies biologicals and to appraise the monitoring and reporting of rabies biologicals at all the levels. Methods: A multicentric survey was conducted from July to December 2017 in seven regional representative states across the country. The survey team visited the offices in-charge for logistics of rabies biologicals at the survey states and districts; information was collected using structured pro formas and perusing relevant records. District vaccine stores and health institutions in urban and rural areas were visited to assess the availability and stock-outs of rabies biologicals. Results: Procurement, distribution, and availability of rabies biologicals grossly vary between states, since it is the state subject. In Gujarat, both vaccines and immunoglobulins were available even at the Primary Health Centre level; paradoxically, there was a scarcity of both at the district level in Manipur. Immunoglobulins were used only in nine of the surveyed 27 government health-care facilities (33.3%) and two of the eight private facilities (25%). The cold chain facility for storage of rabies biologicals was satisfactory; however, the monitoring and reporting of rabies biologicals were not complete. Conclusion: The procurement, distribution, availability, and utilization of rabies biologicals were not universal across the states. Frequent shortages of supply have to be improved to attain universal coverage.